Sensorimotor integration of vestibular, proprioceptive, and visual information about head motion in the interpretation of dynamic auditory cues for front/back sound localization - Macpherson, Ewan A; Kim, Janet (Canadian Acoustics, 2016)
Accurate perception of the location of a sound source is greatly facilitated by listener head rotation, which generates dynamic interaural time- and level-difference cues that differ between front- and rear-hemisphere sources. Those cues, however, specify front/back location only when coupled with information about the head motion that produced them. Potential sources of head-motion information for the auditory system are the vestibular, proprioceptive, and visual systems. To investigate the influence of these extra-auditory modalities on the interpretation of dynamic acoustic cues, we have examined dynamic localization performance using an oscillating chair apparatus that permits dissociation of head-on-body and head-in-space motion in combination with a pair of left/right-reversing prism glasses that provide incongruent visual motion information. The results suggest that vestibular (head-in-space) information is necessary and sufficient for accurate interpretation of the dynamic cues, whereas proprioceptive (head-on-body) information is neither necessary nor sufficient. Incongruent visual input has little or no influence on listeners’ interpretation of the dynamic auditory cues. Additionally, the temporal dynamics of dynamic cue processing seem to be particular to auditory-vestibular integration.